TssA forms a gp6-like ring attached to the type VI secretion sheath - Planamente,S; Salih,O; Manoli,E; Albesa-Jove,D; Freemont,PS; Filloux,AAM (EMBO Journal, 2016)
The type VI secretion system (T6SS) is a supra-molecular bacterial complex that resembles phage tails. It is a killing machine which fires toxins into target cells upon contraction of its TssBC sheath. Here, we show that TssA1 is a T6SS component forming dodecameric ring structures whose dimensions match those of the TssBC sheath and which can accommodate the inner Hcp tube. The TssA1 ring complex binds the T6SS sheath and impacts its behaviour in vivo. In the phage, the first disc of the gp18 sheath sits on a baseplate wherein gp6 is a dodecameric ring. We found remarkable sequence and structural similarities between TssA1 and gp6 C-termini, and propose that TssA1 could be a baseplate component of the T6SS. Furthermore, we identified similarities between TssK1 and gp8, the former interacting with TssA1 while the latter is found in the outer radius of the gp6 ring. These observations, combined with similarities between TssF and gp6N-terminus or TssG and gp53, lead us to propose a comparative model between the phage baseplate and the T6SS.